Ibu hamil perokok pasif sebagai faktor risiko bayi berat lahir rendah - Irnawati Irnawati; Mohammad Hakimi; Tunjung Wibowo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Low birth weigth babies (LBW) are most likely a cause of the infant mortality and morbidity. Many factors causes LBW babies as maternal health, behavior during pregnancy, environmental as well as fetal and placental factors. Negative behavior during pregnancy such as exposure of cigarette smoke can affect the body’s supply of oxygen from mother to fetus and placenta. Exposure to cigarette smoke may also reduce maternal folic acid level which causes disruption of fetal growth inside the womb.Objective: This study was aimed to fnd out the risk of low birth weight baby in the passive smoker pregnant woman.Method: The study used a case control design. The subject consisted of mothers who delivered at RSU dr. Zainoel Abidin in Banda Aceh municipality. The case group were mothers who delivered babies of less than 2,500 grams and the control group were those who delivered babies of 2,500 grams or more. Each group consisted of 105 mothers (1:1). Sample were taken using non probability with consecutive sampling method. Data analysis used univariable method with frequency distribution, bivariable with chi square and multivariable with logistic regression.Results: Passive smoker pregnant woman exposed the 1-10 cigarettes a day had risk 2,4 times greater of getting low birth weight baby (OR=2,42; 95%CI 1,24-4,71). Pregnant mother exposed to ≥11 cigarettes a day had the risk 3,1 times greates in having LBW infants than those not exposed (OR=3,1; 95%CI 1,50-6,70).Conclusion: Passive smoker of pregnant mother increased the risk of low birth weight babies.